Risk of pancreatic fistula after enucleation of pancreatic tumours. Issue 10 (24th June 2015) - Strobel, O; Cherrez, A; Hinz, U; Mayer, P; Kaiser, J; Fritz, S; Schneider, L; Klauss, M; Büchler, M W; Hackert, T
Abstract: Background: Enucleation is used increasingly for small pancreatic tumours. Data on perioperative outcome after pancreatic enucleation, especially regarding the significance and risk factors associated with postoperative pancreatic fistula (POPF), are limited. This study aimed to assess risk-dependent perioperative outcome after pancreatic enucleation, with a focus on POPF. Methods: Patients undergoing enucleation for pancreatic lesions between October 2001 and February 2014 were identified from a prospective database. A detailed analysis of morbidity was performed. Risk factors for POPF were assessed by univariable and multivariable analyses. Results: Of 166 enucleations, 94 (56·6 per cent) were performed for cystic and 72 (43·4 per cent) for solid lesions. Morbidity was observed in 91 patients (54·8 per cent). Severe complications occurred in 30 patients (18·1 per cent), and one patient (0·6 per cent) died. Reoperation was necessary in nine patients (5·4 per cent). POPF was the main determinant of outcome and occurred in 68 patients (41·0 per cent): grade A POPF, 34 (20·5 per cent); grade B, ten (6·0 per cent); and grade C, 24 (14·5 per cent). Risk factors independently associated with POPF were: cystic tumour, localization in the pancreatic tail, history of pancreatitis and cardiac co-morbidity. Only cystic morphology was independently associated with clinically relevant POPF (grade B or C), occurring after enucleation in 25 (27 per cent) of 94 patients with cystic tumours versus nine (13 per cent) of 72 patients with solid tumours. Tumour size and distance to the main duct were not associated with risk of POPF. Conclusion: Enucleation is a safe procedure in appropriately selected patients with a low rate of severe complications. POPF is the main determinant of outcome and is more frequent after the enucleation of cystic lesions. Abstract : Safe in an expert centre